IMPLEMENTATION OF SCIENTIFIC APPROACH TO JURISPRUDENCE IN MADRASAH TSANAWIYAH NEGERI 2 MEDAN - Siti Nurzannah; Rusydi Ananda (Universitas Islam Negeri Sumatera Utara Medan, 2019)
The purpose of this study is: (1) To find out the design of learning thatuses a scientific approach to learning Jurisprudence in MTs Negeri 2Medan, 2) To find out the implementation of the scientific approach tolearning Fiqh in MTs Negeri 2 Medan, 3) To find out the obstacles inimplementing the scientific approach to Jurisprudence learning fiqih inMTs Negeri 2 Medan, 4) To find out the efforts to overcome it in theimplementation of the scientific approach to Jurisprudence learning fiqihin MTs.Negeri 2 Medan, 5) To find out the views of Jurisprudence teacherson the implementation of the scientific approach to Jurisprudence learningfiqih in MTs.Negeri 2 Medan, 6) To find out the views of students on theimplementation of the scientific approach to Jurisprudence learning fiqihin MTs.Negeri 2 Medan, 7) To find out the views of parents on theimplementation of the scientific approach to learning Fiqh in MTs.Negeri2 Medan. This research was carried out in Madrasah Tsanawiyah Negeri 2Medan addressable in Jl. Peratun No. 3 Komplek Medan Estate. This typeof research is qualitative research, Observation data collection techniques,Interviews, Field Notes, Documentation. The results of this study indicatethat the design of the Scientific approach was carried out by theJurisprudence teachers earlier before the beginning of the semester. Inpreparing the RPP the teacher also examines the syllabus and looks at KIand KD in the lesson plan. The implementation of the Scientific approachhas been carried out by the Jurisprudence teacher quite well, but theimplementation has not been maximized. Barriers to implementation of the Scientific approach include obstacles when drafting the RPP, and Implementation of 5M.